1965
DOI: 10.1029/jz070i019p04921
|View full text |Cite
|
Sign up to set email alerts
|

Further investigations of a variation of geomagnetic activity with lunar phase

Abstract: The previously studied variation of geomagnetic activity with lunar phase indicates a g,eneral decrease in geomagnetic activity of about 4% for several days before full moon and an increase of about 4% for several days after full moon. Substantial evidence is presented indicating that the observed variation of geomagnetic activity with lunar phase requires lunar latitudes at full moon within about 4 ø from the ecliptic plane. It is demonstrated that the influence of a variable lunar parallax must be .extremely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…[1964] were, however, unable to find any dependence of terrestrial magnetic activity on lunar phase. Stolov [1965] has found that the observed variation of geomagnetic activity with lunar phase requires lunar latitudes at full moon within about 4 ø from the ecliptic plane, a distance of approximately 4 RE.…”
Section: Numerious Theories Have Been Brought Forthmentioning
confidence: 99%
“…[1964] were, however, unable to find any dependence of terrestrial magnetic activity on lunar phase. Stolov [1965] has found that the observed variation of geomagnetic activity with lunar phase requires lunar latitudes at full moon within about 4 ø from the ecliptic plane, a distance of approximately 4 RE.…”
Section: Numerious Theories Have Been Brought Forthmentioning
confidence: 99%
“…(2) Comparison with random or "randomized 11 data [Stolov andCameron, 1964, Stolov, 1965;Davidson and Martyn, 1964] , and ,…”
Section: The Solar Effect At the Lunar Periodmentioning
confidence: 99%
“…The 24.8-hour lunar day, on the other hand, leads to a tidal cycle of 12.4 h, with high tides when the Moon is positioned directly above the sea water or on the point diametrically opposed on the other side of the planet. Finally, the deviation of the Moon's orbit from the Earth's equatorial plane causes the amplitude of the semidiurnal tides (with a period of 12.4 h) to be asymmetrical, leading a semidiurnal inequality in the tides, in some cases so unequal that there is only one significant ebb of water every 24.8 h and not every 12.4 h [5,6]. All these environmental changes can be perceived by animals and plants, affect their behaviour, physiology, the adaptive significance of performing certain activity at a certain time and ultimately affect their fitness.…”
Section: Introductionmentioning
confidence: 99%